Isorhamnetin Attenuates Isoproterenol-Induced Myocardial Injury by Reducing ENO1 (Alpha-Enolase) in Cardiomyocytes - Zhenli Guo; Shizhong Liu; Xianghong Hou; Xin Zhou; Yan Wang; Yi Rong; Xinzhi Li; Rui Yang; Ketao Ma (Antioxidants)
The protective effect of isorhamnetin on myocardial injury induced by isoproterenol (ISO) was investigated to identify the key targets and pathways involved, offering potential therapeutic insights for cardiovascular diseases. A myocardial injury model was established through intraperitoneal ISO injection, and the effects of isorhamnetin on apoptosis and oxidative stress in ISO-induced myocardial injury rats were assessed. Additionally, an ISO-induced H9c2 cell injury model was established to evaluate the impact of isorhamnetin on cellular damage. The transcriptomic sequencing of H9c2 cells was conducted to identify differentially expressed genes, followed by gene enrichment analysis. Intracellular glucose, lactate, and ATP levels were quantified, and the protein expression of key pathway targets ENO1, PPARα, and PGC-1α was analyzed via immunoblotting. Isorhamnetin improved cardiac function and morphological damage, reduced serum markers of cardiac injury, and exerted cardioprotective effects by regulating oxidative stress and inhibiting apoptosis. Compared to the ISO group, the glycolytic process—with ENO1 as a key target and the PPAR signaling pathway as the core regulator—was significantly suppressed in the isorhamnetin-pretreated group. Furthermore, isorhamnetin pretreatment reduced intracellular glucose and lactate levels while increasing ATP content in a concentration-dependent manner. These findings suggest that isorhamnetin protects the heart by inhibiting ENO1, activating the PPARα/PGC-1α signaling axis, reversing isoprenaline-induced metabolic shifts in H9c2 cells, suppressing glycolysis, and enhancing ATP release, thereby mitigating apoptosis and oxidative stress.